Comportamiento agronómico del cultivo de cebolla roja (Allium cepa L.) con diferentes abonos orgánicos en el colegio Pueblo Nuevo cantón El Empalme, año 2014. - Quishpe Caiza, Kleber Lenin (2015)
This research was conducted at the Agricultural Technical College "Pueblo Nuevo", belonging to the parish The Guayas, El Empalme Canton, is located between the geographical coordinates 01 ° 06' south latitude and 79 ° 29 west longitude at an altitude of 73 m. The duration of the research was 120 days.Design Randomized Complete Block (DBCA), with seven treatments and four replications. For the determination of the means was resorted to using multiple range test of Tukey 95% probability. Treatment best leaf length and more leaves was obtained T5 (Dunger 3 kg) treatment with an average of 36.78 cm at forty-five days and 5.37 respectively leaves. The best form of treatment was the T7 throw bulb (Control) with an average of 59.75, while the T3 (Humus 5kg) demonstrated positive values referring to bulb diameter with 5.10 cm. The treatment showed better weight bulb T3 (Humus 5 kg) treatment with an average value of 86.67 gr, establishing that the variable weight is of great importance in culture. For the analysis of the benefit / cost treatment presented best economic value was T3 (Humus 5kg) ie for every dollar invested profit of $ 1.42 is generated.